A case of gastrointestinal stromal tumor presenting with small bowel perforation and internal hernia - Volkan ÖZBEN,; Sinan Çarkman,; Deniz ATASOY,; Gülen DOĞUSOY,; Erhun EYÜBOĞLU, (Turkish Journal of Gastroenterology, 2019)
-